Use of Artificial Intelligence in Nononcologic Interventional Radiology: Current State and Future Directions - Malpani, Rohil; Petty, Christopher W.; Bhatt, Neha; Staib, Lawrence H.; Chapiro, Julius (Digestive Disease Interventions, 2021)
The future of radiology is disproportionately linked to the applications of artificial intelligence (AI). Recent exponential advancements in AI are already beginning to augment the clinical practice of radiology. Driven by a paucity of review articles in the area, this article aims to discuss applications of AI in nononcologic IR across procedural planning, execution, and follow-up along with a discussion on the future directions of the field. Applications in vascular imaging, radiomics, touchless software interactions, robotics, natural language processing, postprocedural outcome prediction, device navigation, and image acquisition are included. Familiarity with AI study analysis will help open the current “black box” of AI research and help bridge the gap between the research laboratory and clinical practice.
Keywords: artificial intelligence; machine learning; radiomics; deep learning; interventional radiology